JP2 Generation Phenomenon - Krzysztof Pawlina (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Generally speaking, young people in Poland do not reject religion. The vast majority of youth declare themselves to be believers. Their faith, however, is characterized by subjectivity and selectiveness. Situationism is a trait of the Polish young generation. They make their choices dependent on something… Gaining a good education, a good job and starting a family are important life goals for young people. The youth of the 21st century are called “the youth without wings”. Those young people do not have any great ideals. They are not attracted by high values of a changing the world, they do not aim at establishing a better social system. The youth of the 90’s used to set up non-governmental organizations, they took up social activity in the third sector. The young people of the 21st century comprise a generation focusing on their own future. It is not a struggling generation but rather one evading or minimizing their activity in spheres which do not bring them direct benefits. Whatever is not practical, needed for today, is discarded.